COLLABORATIVE GOVERNANCE IN THE REVITALIZATION OF TRADITIONAL MARKETS: A LITERATURE REVIEW OF PASAR PALANG SUKOREJO PASURUAN - Laili Fitriyah; Aminullah (International Journal of Multidisciplinary Reseach, 2026)
Traditional markets play a crucial role in supporting people's economies, but face various challenges such as declining infrastructure quality, competition with modern markets, and changes in people's spending patterns. One of the steps to strengthen the competitiveness of the traditional market is to implement a revitalization program. This study aims to analyze collaborative governance in the revitalization of the Sukorejo Cross Market in Pasuruan Regency based on a literature review and identify the role of stakeholders, supporting factors, and obstacles in its implementation. This research applies a qualitative approach through the literature study method. Information is drawn from academic journals, books, government documents, official reports, and other relevant written sources. Data analysis is carried out through content studies by identifying, grouping, and interpreting information from various sources. The research findings show that the revitalization of the Sukorejo Cross Market requires the implementation of collaborative management involving the local government, market managers, traders, and the community. Supporting factors include efficient communication, active involvement of traders, as well as the government's dedication to policy design and budget allocation. Inhibiting factors include traders' disapproval of change, lack of transparency of information, and weak coordination between institutions. This research indicates that the success of the revitalization of traditional markets is determined not only by physical improvements, but also by effective cooperation among stakeholders.